Sentence Fragments in Student’s Composition - Bella Safira Pratiwi (IALLTEACH (Issues In Applied Linguistics & Language Teaching), 2017)
The aim of this research is to analyze several categories of sentence fragments in student’s composition as well as to ascertain the source of the errors from the questionnaire that given by the researchers. The researchers utilize the approaches of St Pit Corder Error Analysis to examine the data. The data are two written text, which appeared to be an English Composition written by eight students of Universitas Balikpapan from fourth semester and five different Departments. The second data is a questionnaire that answered by the eight participantsdifferently. The researchers found five variants of sentence fragments that made by the students in their English compositions. The five types of sentence fragments are the absence of subject, absence of verb, uncompleted thought, incomplete verb, and complex errors. The questionnaire demonstrate that the incomplete knowledge of English is the source of student’serrors. This type of errors is known as Intralingual errors.